CONSENSUS AND DISSENT. AN APPROACH TO THE POLITICAL CONCEPTION PROPOSED IN THE THESES OF THE LAW STUDENT OF COÌRDOBA AND BUENOS AIRES (1880-1910) - Navarro, Hans Cristian Jaid Tepos (Revista de Historia Social y de las Mentalidades, 2022)
One of the significant actors in political and social life during the late nineteenth and early twentieth centuries in Argentina, although little analyzed, were law students due to their possibility of political participation through their mobilizations, groups, and academic writings. The purpose of this article is to analyze the theses written by students of the Law Faculties of Córdoba and Buenos Aires to understand how they conceived of the state, what characteristics they assigned to the political system they considered to be suitable and, in doing so, to give an account of their tendencies, which will allow us to broaden our understanding of the plurality and evolution in their positions.
Keywords: Thesis; Political Conception; Students of Law; Political System; Political History